Susceptibility Factors of Stomach for SARS-CoV-2 and Treatment Implication of Mucosal Protective Agent in COVID-19 - Zhang, Min; Feng, Chao; Zhang, Xingchen; Hu, Shuofeng; Zhang, Yuan; Min, Min; Liu, Bing; Ying, Xiaomin; Liu, Yan (Frontiers in Medicine, 2021)
Background & Aims： To study the gastrointestinal (GI) symptoms in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infected patients and susceptibility factors of stomach for SARS-CoV-2. Methods：We investigated the SARS-CoV-2 susceptibility by analyzing the expression distribution of viral entry-associated genes, ACE2 and TMPRSS2, in single cell RNA sequencing data derived from 12 gastric mucosa samples. We also analyzed epidemiological, demographic, clinical and laboratory data of 420 cases with SARS-CoV-2 caused coronavirus disease 2019 (COVID-19). Results：ACE2 and TMPRSS2 are specifically expressed in enterocytes which are mainly from gastric mucosa samples with helicobacter pylori (H. pylori) infection history and intestinal metaplasia (IM). A total of 420 patients were surveyed, of which 62 with and 358 without GI symptoms. There is a significant difference in average hospital stay (p < 0.001) and cost (p < 0.001) between two groups. Among 23 hospitalised patients including 7 with upper GI symptoms and 16 with lower GI symptoms, 6 (85.7%) and 5 (31.3%) had H. pylori infection history, respectively (p=0.03). Of 18 hospitalised patients with initial upper GI symptoms, none of the 8 patients with mucosal protective agent therapy (e.g. sucralfate suspension gel, hydrotalcite tablets) had diarrhea subsequently whereas 6 out of 10 patients without mucosal protective agent therapy had diarrhea subsequently (p = 0.01). Conclusions：IM and H. pylori infection history may be susceptibility factors of SARS-CoV-2, and mucosal protective agent may be useful for blockade of SARS-CoV-2 transmission from stomach to intestine.